Christian A. Fleetwood papers - Fleetwood, Christian A. (Christian Abraham), 1840-1914.; Fleetwood, Sara Iredell
Correspondence, diaries (1862-1864), legal documents, scrapbook, printed material, memorabilia, and photographs pertaining chiefly to Fleetwood's service with the 4th Colored Infantry Regiment, U.S. Army, during the Civil War and to his activities as a leading African-American citizen of Washington, D.C. Subjects include education, nursing, slavery, and other civic and social concerns of the African American community in the District of Columbia where Fleetwood held various government and business positions. Includes papers of his wife, Sara Iredell Fleetwood, relating to her career as a nurse and correspondence of other family members.
Microfilm edition available
Microfilm produced from originals in the Library of Congress.
Soldier and civic leader.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Fleetwood family -- Correspondence; United States. -- Army. -- Colored Infantry Regiment, 4th (1863-1866); African Americans -- Education; African Americans -- Social conditions; African Americans -- Washington (D.C.); Medal of Honor; Nursing; Slavery -- United States; United States -- History -- Civil War, 1861-1865 -- African Americans; Civic leaders; Soldiers